Exploring the effects of medicinal fungi on isolated bladder strips (ex vivo) and Caenorhabditis elegans (in vivo): focus on the caterpillar fungus, Ophiocordyceps sinensis - Pang, Li Yin (2024)
Medicinal fungi have been traditionally used to treat many medical conditions. Today, they remain a major source of new pharmaceutical products due to the presence of a plethora of bioactive components. In China and several East Asian countries, Ophiocordyceps sinensis, one of the most sought-after medicinal fungi, is widely used for alleviation of urinary symptoms such as frequent urination and nocturia – the two most common symptoms of overactive bladder syndrome (OAB). Despite this, there is no credible scientific evidence that links the effect of O. sinensis to bladder function. Therefore, this study was initiated to explore the therapeutic potential of medicinal fungi in OAB due to the limitations of the current conventional treatment options, and to provide scientific validation of O. sinensis in alleviating OAB symptoms. Specifically, the principal aim of this study was to investigate the pharmacological actions of O. sinensis extract in bladder by using the isolated tissue bath technique. The secondary aim was to provide evidence on its health benefits, given its established antioxidant properties and that OAB is highly prevalent in the geriatric population. A cultivated strain of O. sinensis (OCS02®) that has been authenticated by genetic identification was utilised in this study.